Incorporating language games to enhance grammar acquisition in the ESL classroom: an exploratory study / Rafhana Roslan - Roslan, Rafhana (2011)
Grammar is essential in second language acquisition. However, English teachers tend to focus on traditional grammar teaching which emphasizes more on the rules rather than meaning. Therefore, language games is suggested as one of the techniques that can create meaningful contexts of language use in the teaching of grammar (Vernon, 2010). As Brown (2003) observes, most games require students to work in pairs or groups and this brings advantage to them as it can create a student-centered environment. This study investigated the effectiveness of language games in the acquisition of grammar among 51 Form One ESL learners of a secondary school. They were divided into the experimental and control group. Specifically, this study seeks to observe which types of language games enhance students’ grammar acquisition. Additionally, the study attempted to investigate the correlation between the use of language games in teaching grammar and students’ test score in English. The research design is an experimental research. Thus, the independent variable was language games and the dependent variable was grammar acquisition of the students, measured in terms of their scores in test. Data obtained from the tests were analyzed using independent sample t-test. The findings of this study revealed that the use of language games did enhance grammatical competence. In addition, there was significant relationship between English test scores of students and the use of language games in teaching. The study concludes with some recommendations to include language games in ESL classroom to enhance students’ grammatical competence.